Garlic and ginger essential oil-based neomycin nano-emulsions as effective and accelerated treatment for skin wounds' healing and inflammation: In-vivo and in-vitro studies - Muhammad Ibrar; Yaseen Ayub; Rabia Nazir; Misbah Irshad; Naqi Hussain; Yasar Saleem; Muhammad Ahmad (Elsevier, 2022)
Skin, largest organ of human, is directly exposed to environment and hence is prone to high rates of injuries and microbial infections. Over the passage of time these microbes have developed resistance to antibiotics making them ineffective especially in lower doses and hence, higher dosages or new drugs are required. The current study deals with designing of nano-emulsion (NE) formulations composed of garlic and ginger oils (0.1 %) with neomycin sulphate used in different ratios (0.001, 0.01 and 0.1 %) and combinations. The resulting NEs were characterized for droplet size (145-304 nm), zetapotential (-3.0-0.9 mV), refractive index (1.331-1.344), viscosity (1.10-1.23cP), transmittance (96-99 %), FT-IR and HPLC and found stable over a period of three months. All NEs were also found effective against both gram positive and negative bacterial strains i.e., B. spizizenii, S. aureus, E. coli and S. enterica as compared to pure neomycin sulphate (NS) used as control with highest activity recorded for NE-2 and NE-4 against all strains showing zone of inhibition in range of 22-30 mm and 21-19 mm, respectively. NEs were also tested using rabbit skin excision wound model which potentiates that all the NEs resulted in early recovery with 86-100 % wound healing achieved in 9 days as compared to NS ointment (71 %). The studies confirmed that essential oils when used in combination with traditional drug can lead to much higher efficacies as compared to pure drugs.